The effect of money attitude, subjective norm, perceived behavioural control, and perceived risk on millennial’s saving intention - Nadia Asandimitra; I Made Narsa; Andry Irwanto; Helmi Ishartanto (BISMA (Bisnis dan Manajemen), 2021)
The Theory of Planned Behaviour (TPB) has been widely applied in the financial sector. However, no research has investigated the moderating role of financial literacy in saving intention. This study investigates the moderating role of financial literacy in the partial influence of money attitude, subjective norms, perceived behavioural control, and perceived risk on saving intention. According to the Moderated Regression Analysis (MRA) findings, financial literacy moderated the effect of money attitude, subjective norms, and perceived behavioural control on saving intention. On the other hand, financial literacy has not mitigated the effect of perceived risk on saving intention. These findings validate TPB's application in the financial sector by incorporating moderating role of financial literacy. It is also discovered that the millennial generations who participate in this study have good financial literacy.